Local Governments and Environmental Policy in Iceland - Kristrún Halla Gylfadóttir 1993- (2021)
The focus of this study is the local governments in Iceland and how they approach environmental policymaking and implementation. This study evaluates the state of environmental policymaking at the local level in Iceland, which issues the policies address, the quality of the policies, and what impacts municipalities’ ability to create and implement environmental policies. A framework was created to evaluate the content and identify the themes of all environmental policies at the local level in Iceland, whether they included factors of good policy-making, and which instruments were used to implement. Based on that information, the policies of six different sized municipalities were further analyzed. The criteria were that those environmental policies had been in place for at least 2 years, included most or all the factors of good policymaking and the municipalities were in different locations in Iceland. Semi-structured interviews were conducted with a representative from each of those six municipalities. Results show that over half of Icelandic municipalities have established environmental policies and the most common themes are waste management and nature protection, which are legally binding for municipalities. All the large municipalities have established environmental policies, and of those with no policy, the majority are small. Most of the policies that meet the criteria of good policymaking are from the municipalities working together with the certification group EarthCheck. Having a larger population and working in networks with other municipalities is favorable when it comes to environmental policymaking and implementation. To strengthen environmental policymaking at the local government level there is a need for more support for smaller municipalities, in the form of clearer guidelines, more funds, resources, and training as well as enhanced cooperation of neighboring municipalities, resulting in sharing of skills and ideas. Þessi rannsókn leggur áherslu á sveitarstjórnir á Íslandi og hvernig þær ...